Nos tempos do blackout: cena musical, práticas urbanas e a ressignificação da Rua Chile, Natal-RN - Cunha, Carlos Henrique Pessoa (2014)
This study aims to analyze the process of resignification of Chile Street, in Natal, from the development of a music scene in the late 1990s. Chile Street, as part of the Historic Centre of Natal, had its images constructed from the discursive practices and everyday life of its regular visitors, leading to a series of symbolic and imaging transformations throughout the twentieth century. Initially transformed into glamorous space as a result of urban actions of the new republic of Albuquerque Maranhão, in the early twentieth century, Ribeira and Chile Street, specifically, came to be seen as bohemian area, during the war time"; followed by a marginal phase, it was eventually transformed into the main rocker area of Natal, with the development of a musical scene in the second half of the 1990s. This music scene, its practices, economic interests, cultural events and identity ties created among their practitioners made Chile Street, "in the time of Blackout night club", an "alternative" space. As the historic centers, inserted in the logic of postmodern city marketing, both spaces are dynamic in their practices, as in their images, Chile Street also suffered changes in its meanings and symbols, around the year 2000 when the alternative-underground space became a pop space, where people from various parts of the city began attending its events and places, transforming it into a point of very heterogeneous sociability